2013
DOI: 10.7314/apjcp.2013.14.7.4131
|View full text |Cite
|
Sign up to set email alerts
|

Allium Vegetables and Risk of Prostate Cancer: Evidence from 132,192 Subjects

Abstract: Objective: To evaluate the relationship between allium vegetable intake and risk of prostate cancer. Methods: A systematic literature search up to May 2013 was carried out in PubMed, EMBASE, Scopus, Web of Science, Cochrane register, and Chinese National Knowledge Infrastructure (CNKI) databases, and the references of retrieved articles were also screened. The summary relative risks with 95% confidence interval for the highest versus the lowest intake of allium vegetables were calculated. Heterogeneity and pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…Similarly to our results, a preventive effect of garlic on gastric cancer was observed in three hospital-based case-control studies (OR = 0·57; 95 % CI 0·34, 0·80) and in eight population-based case-control studies (OR = 0·52; 95 % CI 0·37, 0·67), while one cohort study showed an increased risk (OR = 1·28; 95 % CI 0·45, 3·66) (39) . Furthermore, the results obtained on prostate cancer were similar to our results in showing that meta-analysis from the case-control studies suggested a significant reduction in risk (OR = 0·77; 95 % CI 0·64, 0·91) while the results from the cohort studies were null (OR = 0·96; 95 % CI 0·89, 1·05) (40) . Several mechanisms have been suggested to participate in Table 2 Results of stratified analysis on the basis of study type, cancer site and sex 0·655 (23,(25)(26)(27)(28)31,33,34) F, females; M, males.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly to our results, a preventive effect of garlic on gastric cancer was observed in three hospital-based case-control studies (OR = 0·57; 95 % CI 0·34, 0·80) and in eight population-based case-control studies (OR = 0·52; 95 % CI 0·37, 0·67), while one cohort study showed an increased risk (OR = 1·28; 95 % CI 0·45, 3·66) (39) . Furthermore, the results obtained on prostate cancer were similar to our results in showing that meta-analysis from the case-control studies suggested a significant reduction in risk (OR = 0·77; 95 % CI 0·64, 0·91) while the results from the cohort studies were null (OR = 0·96; 95 % CI 0·89, 1·05) (40) . Several mechanisms have been suggested to participate in Table 2 Results of stratified analysis on the basis of study type, cancer site and sex 0·655 (23,(25)(26)(27)(28)31,33,34) F, females; M, males.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies suggest that consumption of vegetables and fruit are associated with a lower risk of developing prostate cancer (Liu et al, 2012;Zhou et al, 2013). Askari et al (2014) conducted a case-control study to evaluate the association between consumption of vegetables and fruit and prostate cancer.…”
Section: Protective Factorsmentioning
confidence: 99%
“…It was observed a significant increment of PC risk associated with Carbohydrate pattern (OR=1.64; 95% CI: 1.35, 2.00; p=0.0001), in the absence of heterogeneity (I 2 =0.00%, p=0.393) ( Table 3). The analysis was performed when a number of data ≥3 were available; 2 The risk estimates ware calculated using the random-effect model; 3 In brackets are indicated the number of articles included in the analysis; 4 Analysis was performed on case-control and cohort studies combined together;…”
Section: Meta-analysismentioning
confidence: 99%
“…Indeed, significant preventive effects have been found for the intake of allium vegetables [4], carrots and coffee [5,6], whereas inconsistent correlation has been observed between PC risk and consumption of tomato and lycopene [7,8], tea [9], fruit and vegetables [10], fiber [11], fat [12], red meat, processed meat and seafood [13]. On the other hand, dairy products, calcium and eggs seem to act as risk factors for PC [13,14].…”
Section: Introductionmentioning
confidence: 99%